Defeating Section 10(1)(o)(ii) of the income tax act within the parameters of South Africa's general anti-avoidance rules - Coetzee, E.S.M. (Liza) (University of Pretoria, 2023)
Mini Dissertation (MPhil (International Taxation))--University of Pretoria, 2021.